Anthropometric Indicators as a Tool for Diagnosis of Obesity and Other Health Risk Factors: A Literature Review - Piqueras, Paola; Ballester, Alfredo; Durá-Gil, Juan V.; Martinez-Hervas, Sergio; Redón, Josep; Real, José T. (Frontiers in Psychology, 2021)
Obesity is characterized by the accumulation of excessive amount of fat mass in the adipose tissue, subcutaneous or inside certain organs. The risk does not lie so much in the amount of fat accumulated as in its distribution. Abdominal obesity (central or visceral) is an important risk factor for cardiovascular diseases, diabetes and cancer, having an important role in the so-called metabolic syndrome. Therefore, it is necessary to prevent, detect and appropriately treat obesity. The diagnosis is based on anthropometric indices that have been associated with adiposity and its distribution. Indices itself, or combination of some of them, conform a big picture with different value to stablish risk. Anthropometric indices can be used for risk identification, intervention, or impact evaluation on nutritional status or health, therefore, they will be called Anthropometric Health Indicators (AHIs). We have found 17 AHIs that can be obtained or estimated from 3D human shapes, being the latter, a non-invasive alternative compared to X-ray-based systems, and more accessible than high-cost equipment. A literature review has been conducted to analyze the following information for each indicator: definition; main calculation or obtaining methods used; health aspect/s associated with the indicator (among others, obesity, metabolic syndrome, or diabetes); criteria to classify the population -by means of percentiles or cutoff points, and based on variables such as sex, age, ethnicity, or geographic area-, and limitations.